May Lwin: Media Technology and Health Communication - Yuehan Xiong (The Journal of Medicine, Humanity and Media, 2026)
Professor May O. Lwin of Nanyang Technological University, Singapore, has long pioneered research at the intersection of media technology and health communication. Her work explores the relationship between technology adoption and health behaviors, combining academic rigor with practical relevance. This paper systematically reviews her academic research landscape using bibliometric methods and tools such as Citespace and VOSviewer. It analyzes 119 publications indexed in the Web of Science Core Collection from 2006 to present, examining dimensions including publication volume distribution, keyword clustering, field overlap, and author collaboration networks. The findings reveal that May Lwin's research centers on specific populations such as minors, with attitudes and behaviors as core measurement dimensions. Her work spans diverse topics including media technology-based health interventions, privacy protection, and cross-subject collaboration, exhibiting distinct evolutionary phases: 2006–2009: Exploring the intervention value of technology in specific health contexts 2010–2014: Focusing on precision and trust-building in health communication within digital media environments 2015–2019: Emphasizing scenario-based adaptation of technology and expansion of diverse pathways 2020–2025: Addressing information asymmetry and equity issues in health communication Its interdisciplinary research paradigm and research orientation focused on socially vulnerable groups provide important theoretical references and practical insights for the field of health communication.